Effect of soil conditions on the cyanide content of cassava (Manihot esculenta Crantz) roots and leaves grown in selected areas in Iloilo, Philippines - Netura, Rizalyn G (University of the Philippines in the Visayas, 2019)
Cassava (Manihot esculenta Crantz), a drought tolerant staple food crop grown in tropical and subtropical regions in the world, has been subject to recent reports due to possibility of chronic poisoning from the presence of cyanide. This possess a major drawback in the maximum use of cassava as food. This study aimed to establish a link between soil conditions such as pH, total nitrogen (N), available phosphorus (P), and exchangeable potassium (K) on the cyanide content of cassava roots and leaves that are grown in selected areas in the Province of Iloilo. Sources of soil and cassava samples included 10 cassava farms in Iloilo. Soil conditions such as pH, N, P, and K were determined to possess the nutrient levels at which the plant was being planted. Results show that the soils in the province of Iloilo differ in all sampling sites. However, most of the sampling sites have soil conditions that are suitable and can support cassava growth. A picrate paper coupled with UV-Vis spectrophotometer was employed in the determination of cyanide levels. The cyanide levels in cassava leaves ranged 1.56 ± 0.24 to 176.57 ± 21.96 mg.kg^(-1) and cyanide levels in cassava roots ranged 18.79 ± 1.88 to 106.76 ± 25.42 mg.kg^(-1). The reported HCN level in cassava leaves from Pototan (101.57 ± 8.87; p<0.01), Passi (176.57 ± 21.96; p<0.01), and Jaro (58.96 ± 10.19; p<0.05) with the standard considered safe for human consumption. It was observed that cyanide concentrations were higher in cassava leaves than in roots in mature plants, which was supported by a significant correlation (r=0.581; p=0.048). Moreover, significant correlation (r=-0.581; p=0.047) was also observed between HCN levels in cassava roots and soil K levels. However, associations between HCN levels and some soil conditions such as pH, N, and P was nonetheless established.